Patient Satisfaction Regarding Food and Nutrition Care in Hospitals of Lahore, Pakistan - Sadaf, Saima; Malik, Ahmed Azam; Bilal, Asma; Saeed, Ayesha (Progress in Nutrition, 2018)
Background: Patient satisfaction surveys regarding nutritional services reflect an overall standard of health; and are necessary to highlight patient concerns. The objective of the current study was to assess patient satisfaction regarding food and nutrition care in hospitals of Lahore, Pakistan. Methods: A cross sectional survey was conducted at two purposefully selected Government tertiary care hospitals. Four hundred patients fulfilling inclusion criteria were enrolled consequently after taking written informed consent. Data on demography was collected through a pretested, structured questionnaire. A validated and reliable instrument “Acute Care Patient Satisfaction Questionnaire” in local language was administered to the patients. Descriptive and inferential statistics were applied accordingly using SPSS version 17. Results: Majority of the patients was aged between 31- 50 years (n=200, 50%). 210 (52.6%) females and 129 (47.3%) male were included in the final sample. Overall 71% and 50 % patients were not satisfied in Sheikh Zayed Hospital and Mayo Hospital respectively (p =<0.001). Logistic regression analysis revealed the level of satisfaction; hospital food (OR=1.724, CI=1.11-2.69, p=0.016*), crockery (OR = 0.948, CI = 0.67-1.33, p=0.0760), staff hygiene (OR= 0.467, CI 0.27-0.80, p=0.006), hospital smell (OR = 0.712, CI 0.49-1.03, p=0.073), disturbance by noise (OR =1.083, CI = 0.76- 1.54, p=0.016*), cooking methods (OR = 1.310, CI = 0.91- 1.89, p=0.015*), meal taste (OR 1.198, CI= 0.79-1.81,p=0.394), staff behavior (OR =1.035, CI = 0.61-1.77, p=0.900), portion sizes (OR =0.996, CI= 0.73-1.35, p=0. 979), temperature of food (OR = 1.065, CI = 055-1.83, p=0. 851), quality of food (OR= 1.581, CI = 1.09- 1.46, p=0.160), satiety (OR = 0.956, CI = 0.61- 1.36, p=0.847). Conclusion: It can be concluded that patients were dissatisfied with food and nutritional services. Thus, hospitals must raise their standards of services as indicated by patient’s feedback in these categories i.e. increased menu items, opportunity of food choice, improved quantity and quality of food, improved physical environment of the wards and staff hygiene.